Detalhes construtivos em obras térreas do sistema light stell framing - Calegari, Alessandra Santana (2015)
This paper addresses the constructive details of a construction located in the city of Corbélia Paraná, in the constructive system named Light Steel Framing, system littleknown in Brazil, that is characterised by the installation of panels of profiles of galvanized steel, which has the main objective having the runtime reduce and the less generation of residues. The ratings were obtained through visisting construtuins in its execution phase, from its fundation to vertical clamping. It was found that, for the sucess of the construction, is vital to have specialist manpower, besides following all the necessary parametres to the assembly.